Cost-effectiveness of a mindfulness-based mental health promotion program: economic evaluation of a nonrandomized controlled trial with propensity score matching - Gerhard Müller; Manuela Pfinder; Christian Schmahl; Martin Bohus; Lisa Lyssenko (BMC, 2019)
Abstract Background Mental health promotion programs have been shown to reduce the burden associated with mental distress and prevent the onset of mental disorders, but evidence of cost-effectiveness is scarce. Objective To evaluate the cost-effectiveness of a mindfulness-based mental health prevention program provided by health coaches in a multi-site field setting in Germany. Methods The single-study based economic evaluation was conducted as part of a nonrandomized controlled trial, comparing the effects of a group-based prevention program to usual care based on propensity score matching. Participants (N = 1166) were recruited via a large statutory health insurance fund. Health outcome was assessed with the Hospital Anxiety and Depression Scale (HADS). Cost outcomes were actually incurred costs compiled from the health insurance' records. Incremental cost-effectiveness ratios (ICER) were analyzed from a societal and a health care perspective for a 12-month time horizon with sampling uncertainty being handled using nonparametric bootstrapping. A cost-effectiveness acceptability curve was graphed to determine the probability of cost-effectiveness at different willingness-to-pay ceiling ratios. Results From a societal perspective, prevention was cost-effective compared to usual-care by providing larger effects of 1.97 units on the HADS (95% CI [1.14, 2.81], p < 0.001) at lower mean incremental total costs of €-57 (95% CI [− 634, 480], p = 0.84), yielding an ICER of €-29 (savings) per unit improvement. From a health care perspective, the incremental health benefits were achieved at additional direct costs of €181 for prevention participants (95% CI [40, 318], p = 0.01) with an ICER of €91 per unit improvement on the HADS. Willingness-to-pay for the prevention program to achieve a 95% probability of being cost-effective compared to usual-care, was estimated at €225 per unit improvement on the HADS score from a societal, and €191 from a health care perspective respectively. Sensitivity analyses suggested differential cost-effect-ratios depending on the initial distress of participants. Limitations Due to the complexity of the field trial, it was not feasible to randomize participants and offer an active control condition. This limitation was met by applying a rigorous matching procedure. Conclusions Our results indicate that universal mental health promotion programs in community settings might be a cost-effective strategy to enhance well-being. Differences between the societal and health care perspective underline the call for joint funding in the dissemination of preventive services. Trial registration German Clinical Trials Registration ID: DRKS00006216 (2014/06/11, retrospective registration).